2023
DOI: 10.3389/fchem.2023.1206380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of propanamide-sulfonamide based drug conjugates as dual inhibitors of urease and cyclooxygenase-2: biological and their in silico studies

Abstract: Derivative synthesis has been a crucial method for altering the effects of already-approved medications, especially to lessen adverse effects and enhance results. Making use of this multi-target approach, a series of naproxen-sulfa drug conjugates was designed and synthesized. The newly designed conjugates were confirmed by spectroscopic techniques like IR, 1HNMR, 13CNMR, and elemental analysis. The conjugates were screened for anti-inflammatory, urease, and cyclooxygenase-2 (COX-2) inhibition. Naproxen conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It has already been reported that isoxazole substituted on the sulfonamide side and electron-withdrawing groups such as fluoro-substituted biphenyl groups on the acetamide side showed better urease inhibition activities as compared to methyl substituent phenyl groups on the acetamide side. Furthermore, guanidine and amino groups on the sulfonamide side showed excellent urease inhibition activities compared to five- and six-membered heterocyclic substituents. , Overall, the electron-withdrawing and -donating groups attached to phenyl groups play a pivotal role in the inhibition activities of urease enzymes. However, this effect largely depends on the overall structure of the molecule under investigation. , …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…It has already been reported that isoxazole substituted on the sulfonamide side and electron-withdrawing groups such as fluoro-substituted biphenyl groups on the acetamide side showed better urease inhibition activities as compared to methyl substituent phenyl groups on the acetamide side. Furthermore, guanidine and amino groups on the sulfonamide side showed excellent urease inhibition activities compared to five- and six-membered heterocyclic substituents. , Overall, the electron-withdrawing and -donating groups attached to phenyl groups play a pivotal role in the inhibition activities of urease enzymes. However, this effect largely depends on the overall structure of the molecule under investigation. , …”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, guanidine and amino groups on the sulfonamide side showed excellent urease inhibition activities compared to five-and six-membered heterocyclic substituents. 26,27 Overall, the electron-withdrawing and -donating groups attached to phenyl groups play a pivotal role in the inhibition activities of urease enzymes. However, this effect largely depends on the overall structure of the molecule under investigation.…”
Section: Structure−activity Relationship (Sar)mentioning
confidence: 99%
See 1 more Smart Citation